Gait Speed Control of Lower Limb Exoskeleton using Soleus Electromyogram Signals - LEE, JONG MIN; Choi, Junho; Inchan Youn; Seung-Jong Kim (EMBC, 2019)
Our recent researches have proposed a prediction method of walking speed during swing phase using activation level of soleus muscles measured with electromyogram (EMG) sensors at push-off phase. This method was applied to control gait speed of a treadmill-based lower limb exoskeleton. EMG sensors were attached to healthy subject’s soleus muscles. The subject wore the exoskeleton and was able to walk at a desired walking speed. Experimental result shows that the method has the potential to improve the effectiveness of robot-assisted gait rehabilitation therapy for post-stroke hemiparetic patients.
Keywords: Gait Speed; Lower Limb Exoskeleton; Electromyogram Signal; Soleus